PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERBANKAN SYARIAH TERDAFTAR BURSA EFEK INDONESIA - Chandra Satria; Yeken Suhiba Putri (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
One of indicator of the nation economic performance is indicated by the amount of investment by business actors involved either directly or indirectly in the participation of shares or a number of investments that occur within one country. Banking financial performance is a description of the achievement of financial management targets, either from the collection of third party funds or channeled back in the form of investment products or other financing. Currently, Islamic finance is growing rapidly with many Islamic financial institutions offering financial products and services based on Islamic law. This Developmental conditions have an influence on the picture of Islamic stock investment in the capital market, althought sharia stock investment is not as big as existing conventional stocks. The purpose of this study is to determine the effect of financial ratios in Indonesian Islamic banks on the movement of the value of their share prices. The method in this research is causal associative through secondary data sources in the form of Islamic bank financial reports in the past few years. The results showed that in partial analysis there was no effect of share prices on the level of Islamic bank financial ratios, while simultaneously, there was an effect of Islamic bank financial ratios on Islamic bank share prices in the capital market